Jane Austen the Reader - Murphy, O. author. aut Link
X, 231 p.
Keywords: Jane Austen the Reader explains Austen's excellence and endurance by showing how her writing developed as a response to the writing of others: as parody, satire, criticism and even, on occasion, homage. Seeing Austen as a critic offers new insights into her creativity, and new interpretations of her novels.